2006
DOI: 10.2298/vsp0610879t
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of serum uric acid levels increasing in the treatment of multiple sclerosis

Abstract: Our results suggested that the treatment approaches based on the elevation of serum uric acid levels might prove beneficial for some MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
24
2
Order By: Relevance
“…They went on to show that by contrast, oral administration of its precursor inosine increased both serum and likely CSF urate levels in MS patients (240). Though several MS trials of urate-elevating inosine did not consistently demonstrate slowed clinical progression, these studies established the feasibility of chronic urate elevation as a neurotherapeutic strategy and identified nephrolithiasis as the most common adverse effect and safety concern (241244). …”
Section: Urate Elevation Therapymentioning
confidence: 99%
“…They went on to show that by contrast, oral administration of its precursor inosine increased both serum and likely CSF urate levels in MS patients (240). Though several MS trials of urate-elevating inosine did not consistently demonstrate slowed clinical progression, these studies established the feasibility of chronic urate elevation as a neurotherapeutic strategy and identified nephrolithiasis as the most common adverse effect and safety concern (241244). …”
Section: Urate Elevation Therapymentioning
confidence: 99%
“…Moreover, inosine showed antinflammatory effects in the central nervous system (CNS) and periphery (Hasko et al, 2000; Rahimian et al, 2010; Jin et al, 1997; Gomez and Sitkovsky, 2003; Shen et al, 2005). Some (Toncev, 2006; Markowitz et al, 2009) but not all (Gonsette et al, 2010) clinical studies have suggested a possible antioxidant protective effect of inosine in multiple sclerosis patients (Markowitz et al, 2009). In these trials inosine consistently elevated serum urate, which was proposed to mediate any protective effect of inosine (Markowitz et al, 2009; Spitsin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in MS have reported lower serum UA in cases as compared to controls, and higher serum UA has been associated with delayed onset of the first neurologic episode, stressing some potential for a preventative role [1820]. Other studies in MS suggest there may be therapeutic value in raising serum UA [2123]. …”
Section: Introductionmentioning
confidence: 99%